A Neighbourhood-Based Trust Protocol for Secure Collaborative Routing in Wireless Mobile D2D HetNets - Usman, AB; Gutierrez, J; Bichi, AB (LJS Publisher and IJCSIS Press, 2018)
Heterogeneous Device-to-Device mobile networks are characterised by frequent network disruption and unreliability of peers delivering messages to destinations. Trust-based protocols has been widely used to mitigate the security and performance problems in D2D networks. Despite several efforts made by previous researchers in the design of trust-based routing for efficient collaborative networks, there are fewer related studies that focus on the peers’ neighbourhood as a routing metrics’ element for a secure and efficient trust-based protocol. In this paper, we propose and validate a trust-based protocol that takes into account the similarity of peers’ neighbourhood coefficients to improve routing performance in mobile HetNets environments. The results of this study demonstrate that peers’ neighbourhood connectivity in the network is a characteristic that can influence peers’ routing performance. Furthermore, our analysis shows that our proposed protocol only forwards the message to the companions with a higher probability of delivering the packets, thus improving the delivery ratio and minimising latency and mitigating the problem of malicious peers ( using packet dropping strategy).
Keywords: Hetrogeneous Networks; Wireless D2D Communications; Trust-Based Protocol; Secure Collabaorative Routing